Home environment: association with hyperactivity/impulsivity in children with ADHD and their non-ADHD siblings. - ANNEY, RICHARD (My University, 2013)
We wished to ascertain if there is an association between symptoms of attention-deficit/hyperactivity disorder (ADHD) and home environment in children with ADHD and non-ADHD siblings, controlling for other environmental measures. METHODS: 96 children with ADHD combined type (ADHD-CT) and their siblings participated in the study. Parent and teacher Conners' rating scales were completed and home environment was assessed using the middle childhood and early adolescent Home Observation for Measurement of the Environment (HOME). ADHD symptoms were assessed for correlation with HOME in children with ADHD-CT and non-ADHD siblings and multiple regression analysis was used to control for gender, socio-economic status, exposure to nicotine, exposure to alcohol in utero, birth weight, gestational age, pregnancy and perinatal risk factors. The presence of oppositional disorders was assessed for association with HOME score in those with ADHD-CT. The multiple regression analysis was repeated controlling for environmental factors and for oppositional disorders in those with ADHD-CT. Oppositional symptoms were assessed for correlation with HOME score in non-ADHD siblings. RESULTS: Teacher-rated hyperactive/impulsive scores correlated with HOME (r=-0.27, P < 0.01) in children with ADHD-CT. This association remained significant when other environmental factors and oppositional disorders were controlled for. Environmental factors and gender contributed to 30% of the variance of ADHD symptoms in ADHD-CT. Parent-rated hyperactive/impulsive scores also correlated with HOME (r=-0.28, P < 0.05) for non-ADHD siblings. An association between HOME and diagnosis of oppositional defiant disorder or conduct disorder was found for children with ADHD-CT and between HOME and oppositional symptoms in non-ADHD siblings. CONCLUSIONS: The home environment has a small but significant association with hyperactive/impulsive symptoms in children with ADHD-CT and non-ADHD siblings. This association remained when other environmental factors were taken into account. Oppositional symptoms are associated with home environment in ADHD-CT and in non-ADHD siblings.
PUBLISHED
Keywords: non-ADHD siblings; non-ADHD siblings; Genes & Society; Neuroscience